Aspects of Semantics and Pragmatics of Dialogue. SemDial 2010, 14th Workshop on the Semantics and Pragmatics of Dialogue - Paweł, Łupkowski; Matthew, Purver (Polish Society for Cognitive Science, 2010)
The papers collected in this book cover a range of topics in semantics and pragmatics of dialogue. All these papers were presented at SemDial 2010, the 14th Workshop on the Semantics and Pragmatics of Dialogue. This 14th edition in the SemDial series, also known as PozDial, took place in Poznań (Poland) in June 2010, and was organized by the Chair of Logic and Cognitive Science (Institute of Psychology, Adam Mickiewicz University). From over 30 submissions overall, 14 were accepted as full papers for plenary presentation at the workshop, and all are included in this book. In addition, 10 were accepted as posters, and are included here as 2-4 page short papers. Finally, we also include abstracts from our keynote speakers. We hope that the ideas gathered in this book will be a valuable source of up-to-date achievements in the field, and will become a valuable inspiration for new ones. We would like to express our thanks to all those who submitted to and participated in SemDial 2010, especially the invited speakers: Dale Barr (University of Glasgow), Jonathan Ginzburg (King's College London), Jeroen Groenendijk (University of Amsterdam) and Henry Prakken (Utrecht University, The University of Groningen). Last but not least, we would like to thank everybody engaged in the workshop organization -- the chairs, the local organizing committee for their hard work in Poznań, and the programme committee members for their thorough and helpful reviews.
Keywords: semantics; pragmatics; dialogue; SemDial; formal semantics; artificial intelligence; computational linguistics; psychology; cognitive science